Pendampingan Pembinaan Karakter Islami Siswa SMK di Bulan Ramadhan - Hanipudin, Sarno; Subki, Taqiyudin; Mulat, Tri (Jaanur ElBarik Indonesia, 2025)
This community service activity aimed to provide Islamic character development for vocational high school (SMK) students during the momentum of the holy month of Ramadan, with a focus on strengthening moral values in everyday life. The target audience was the students of SMK Negeri Wanareja, who are in their teenage years—a crucial phase for shaping values and behavior. The methods used in this activity included interactive lectures, group discussions, case studies, and written reflections. The entire program was designed not only to deliver knowledge but also to engage participants in reflecting, discussing, and internalizing Islamic moral values in a contextual and practical manner. The results of the activity showed that the majority of participants (over 85%) actively took part in the sessions and responded to the materials enthusiastically. Based on the questionnaire results, 87% of students felt the activity was beneficial and broadened their understanding of applying Islamic ethics in the digital era. Furthermore, 81% stated that group discussions helped them gain a deeper and more relevant understanding of moral values in relation to the real-life situations they face as teenagers. In conclusion, this activity successfully served as an effective character development initiative and was well-received by the participants. It demonstrates that a dialogical and reflective approach is highly appropriate for conveying moral and ethical values to young people, particularly within the spiritual atmosphere of Ramadan.